2008
DOI: 10.1002/jobm.200700389
|View full text |Cite
|
Sign up to set email alerts
|

Development of a defined medium for heterologous expression in Leishmania tarentolae

Abstract: A defined medium is essential for studying nutritional requirements of microorganisms and for selective supplementation of necessary substances. Hemin is an essential ingredient for growth of Leishmania tarentolae, but tends to precipitate in aqueous solutions without further stabilization. These aggregates disturb the measurement of the optical density or the cell density and the following downstream processing. Therefore, we were looking for stabilizing substances and established a PEG-hemin-solution, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…Supernatants of ultracentrifuged samples were analyzed. For protein purification, culture volume was scaled-up using nine 150 cm 2 -tissue culture flasks each containing 60 mL non-selective YE medium [4]. After pooling all cultures, cells were centrifuged and the cell pellet was either stored at -80°C until use or immediately resuspended in standard Tris buffer supplemented with protease inhibitors (1 mM PMSF, EDTA-free protease inhibitor cocktail).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supernatants of ultracentrifuged samples were analyzed. For protein purification, culture volume was scaled-up using nine 150 cm 2 -tissue culture flasks each containing 60 mL non-selective YE medium [4]. After pooling all cultures, cells were centrifuged and the cell pellet was either stored at -80°C until use or immediately resuspended in standard Tris buffer supplemented with protease inhibitors (1 mM PMSF, EDTA-free protease inhibitor cocktail).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, however, Fritsche et al . developed an alternative growth medium containing hemin, an iron-containing porphyrin essential for growth of Leishmania tarentolae , as the only animal ingredient [4]. Hemin has been shown to stimulate cell proliferation and protein synthesis in L. donovani [5].…”
Section: Introductionmentioning
confidence: 99%
“…Other chemically defined media have been described for L. tarentolae cultivation [33,34] but unfortunately, only complex (BHI-medium) allowed to obtain high-cell densities of Leishmania species. Interestingly, Fritsche et al [35,36] reported L. tarentolae growth behavior in yeast extract-based medium (YE), containing buffer salts and hemin. Large-scale fermentation (2 l) resulted in a small doubling time (6.7 h) and high cell density 0.65-1 9 10 9 cell/ml, about five times higher than reported by Meehan et al with hemin supplemented Brain Heart Infusion media [30].…”
Section: Expression In Fermentor Culturesmentioning
confidence: 98%
“…As shown in Figure 3, IgG2a and IgG1 levels were 9 significantly higher in groups I and II injected with VLPs than those in control group (p <0.05).…”
Section: Immunization With Hpv16 L1 Vlp Induces the Mixture Of Igg1 Amentioning
confidence: 49%
“…Leishmania tarentolae (L. tarentolae) shows some benefits compared to the mammalian cell lines such as: a) the parasite is non-pathogenic for human; b) it is fairly easy to cultivate; c) it produces suitable recombinant protein yields (0.1-30 mg/L or more than), and d) it can easily be improved to an industrial scale [8][9][10][11]. Furthermore, development of constitutive and inducible-integrative expression vectors for Leishmania led to the generation of secretory or intracellular recombinant proteins.…”
Section: Introductionmentioning
confidence: 99%